2014
DOI: 10.5005/jp-journals-10005-1259
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Microleakage in Conventional and RMGIC Restorations following Conventional and Chemomechanical Caries Removal: An in vitro Study

Abstract: ABSTRACT%Background: Conventional caries removal involves use of high-speed handpiece. Current concepts of caries excavation in cavitated lesions consist of manual excavators. Principles of minimal invasive approach indicate the need to excavate only carious tissue.Aim: The aim of this study was to compare the microleakage in conventional and resin modified glass ionomer cement restorations following conventional and chemomechanical caries removal.Design: Hundred class I carious human mandibular first molar s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…[ 27 55 ] Some studies, on the other hand, have found no significant difference in microleakage between conventional GIC and RMGIC. [ 56 57 58 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 55 ] Some studies, on the other hand, have found no significant difference in microleakage between conventional GIC and RMGIC. [ 56 57 58 ]…”
Section: Discussionmentioning
confidence: 99%
“…The mode of caries removal may affect the bond quality and adhesion of restorative material to the tooth structure to a considerable extent. In the year 2014 Pavuluri et al (18) stated that various techniques of caries removal result in different surface textures of excavated dentin and thickness of smear layer which can affect the quality of bonding to dentin and marginal seal (19,20). In the year 2011 El Kassas et al (5) demonstrated that caries excavation with carbide bur led to a relatively compact smear layer while the ceramic bur produced a less compact and more porous smear layer.…”
Section: Discussionmentioning
confidence: 99%
“…Then the samples were immersed in one percent methylene blue for 24h. Subsequently, samples were rinsed with pumice to remove the superficial dye (18). Degree of dye penetration was assessed under a stereomicroscope (Olympus SZ1145, Optical Co., LTD. Tokyo, Japan) at x20 magnification, the image appears on computer screen (Toup view, version 3.7, 2018).…”
Section: Study Outcome Microleakage Evaluation Through Dye Penetration Scores As Well As Distance Of Stain Penetration In Millimetersmentioning
confidence: 99%
“…In many studies on microleakage, the level of leakage was measured with scoring method (Diwanji, Dhar, Arora, Madhusudan, & Rathore, 2014;Pavuluri, Nuvvula, Kamatham, & Nirmala, 2014;Shahidi et al, 2009;Singla, Pandit, Srivastava, Gugnani, & Gupta, 2012;Yilmaz & Misirlio glu, 2013). It was observed that 10-20% of the results differed from the rest of the results when the level of leakage was scored by more than one researcher.…”
Section: Discussionmentioning
confidence: 99%